Bacteremia due to the fastidious bacterium Granulicatella adiacens: a diagnosis that was almost missed - Ding, C. H.; Wahab, A. A.; Mohamed, Nurdiyana; Wong, P. F. (Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2025)
Bacteremia due to Granulicatella adiacens has been rarely reported in the medical literature. A middle-aged gentleman developed necrotizing fasciitis on his left second toe after stepping on a nail. A ray amputation was performed and ceftazidime-susceptible Pseudomonas aeruginosa was isolated from his bone culture. However, while receiving ceftazidime for the necrotizing fasciitis, his blood culture vial was positive for gram-positive cocci-shaped bacteria in short chains which grew as tiny non-lytic colonies on sheep blood agar only following extended incubation. There was no culture evidence of P. aeruginosa in the same blood specimen. The gram-positive organism was conclusively identified by matrix-assisted laser desorption ionization-time of flight mass spectrometry as G. adiacens. The patient was treated with benzylpenicillin (to which the organism tested susceptible) for 14 days before he was discharged home. © 2025, Malaysian Society for Parasitology. All rights reserved.